Five Preference-Based Indexes In Cataract And Heart Failure Patients Were Not Equally Responsive To Change - Kaplan, Robert M. (2010)
OBJECTIVE: To compare the responsiveness to clinical change of 5 widely used preference-based health-related quality-of-life indexes in two longitudinal cohorts. STUDY DESIGN AND SETTING: Five generic instruments were simultaneously administered to 376 adults undergoing cataract surgery, and 160 adults in heart failure management programs. Patients were assessed at baseline and reevaluated after 1 and 6 months. The measures were the SF-6D (based on responses scored from SF-36v2(™)), Self-Administered Quality of Well-being scale (QWB-SA), the EQ-5D developed by the EuroQoL Group, the Health Utilities Indexes Mark 2 (HUI2) and Mark 3 (HUI3). Cataract patients completed the National Eye Institute Visual Functioning Questionnaire (VFQ-25) and heart failure patients completed the Minnesota Living with Heart Failure Questionnaire (MLHFQ). Responsiveness was estimated by the Standardized Response Mean (SRM). RESULTS: For cataract patients, mean changes between baseline and 1 month follow-up for the generic indices ranged from 0.00 (SF-6D) to 0.052 (HUI3) and were statistically significant for all indexes except the SF-6D. For heart failure patients, only the SF-6D showed significant change from baseline to 1 month, while only the QWB-SA change was significant between 1 and 6 months. CONCLUSIONS: Preference-based methods for measuring health outcomes are not equally responsive to change.